Daya Saing Kuliner Tradisional Sunda-Jawa melalui Strategi Harga Kompetitif dan Pemasaran Digital pada Warung Kapungkur - Zaky Ilham Maulana; Hani Humaeriyah (Indo Publishing, 2026)
This study aims to analyze the business feasibility of Warung Kapungkur in Bandung, specifically from a marketing perspective. In the midst of intense competition in the modern culinary industry, Warung Kapungkur combines traditional Javanese-Sundanese culinary concepts with digital marketing strategies to attract consumers, particularly students and workers.The research employs a descriptive qualitative and quantitative method through surveys conducted with respondents in the Bandung area. The marketing analysis is performed using the 4P marketing mix approach (Product, Price, Place, Promotion) and the Segmenting, Targeting, and Positioning (STP) strategy.The findings indicate that in terms of Segmentation, the primary target market consists of consumers aged 15–50 who prefer home-cooked meals at affordable prices. Regarding the Product aspect, respondents provided highly positive feedback on consistent taste and hygiene of the menu, such as